The suppression of He bubble growth in Ni-Mo-Cr alloy by yttrium doping: Irradiation experiment combined with the first-principles calculation. (15th March 2023) - Hui, Jun; Liu, Min; Li, Qiqi; Liu, Renduo; Li, Xiaoli; Wang, Biao
Abstract: In this study, effects of Y on the growth of He bubbles in Ni-Mo-Cr alloy were investigated by irradiation experiment and first-principles calculations. Transmission electron microscope (TEM) characterization revealed that the size of He bubbles in Ni-Mo-Cr alloy was decreased by adding 0.05 wt.% Y. First-principles calculations were then performed to explore the effects of Y on the He behavior in Ni-Mo-Cr alloy. The chemical potential, solubility energy and binding energy of these elements were examined to identify their states. It was found that He could be attracted to Y. The ability of the Y to inhibit He diffusion in Ni-Mo-Cr alloy through transition state was further investigated. The calculation results indicated that strong bonds were formed between Y and He. The motion trails of He atoms at 973 K in Ni-Mo-Cr alloy without and with Y were simulated by AIMD, which showed that He preferred to stably bond with Y. Graphical abstract: Image, graphical abstract